2010
DOI: 10.1002/dvdy.22328
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of embryonic lymphangiogenesis advances the use of the zebrafish model for research in cancer and lymphatic pathologies

Abstract: Lymphangiogenesis induced during tumor growth contributes to metastasis. Genetic and chemical screens using the zebrafish model have the potential to enhance our understanding of lymphangiogenesis, and lead to the discovery of pharmacological agents with activity in the lymphatic system. Large-scale screening of lymphatic development in the whole zebrafish embryo requires a specific lymphatic endothelial cell marker. We isolated the zebrafish ortholog of Lyve1, and analyzed its expression pattern during embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 36 publications
1
40
0
2
Order By: Relevance
“…The recent generation of new, robust transgenic lines that label the venous and lymphatic vascular systems in zebrafish has uncovered previously uncharacterised lymphatic vascular beds and modes of embryonic lymphangiogenesis (Flores et al, 2010;Okuda et al, 2012). These lymphatic vessels include the facial lymphatics (FLs) [also observed previously (Yaniv et al, 2006;Bussmann et al, 2010)] (Fig.…”
Section: Zebrafishmentioning
confidence: 96%
“…The recent generation of new, robust transgenic lines that label the venous and lymphatic vascular systems in zebrafish has uncovered previously uncharacterised lymphatic vascular beds and modes of embryonic lymphangiogenesis (Flores et al, 2010;Okuda et al, 2012). These lymphatic vessels include the facial lymphatics (FLs) [also observed previously (Yaniv et al, 2006;Bussmann et al, 2010)] (Fig.…”
Section: Zebrafishmentioning
confidence: 96%
“…LYVE-1 is extensively used as a marker for lymphatic vessels in mice and humans, and we found zebrafish lyve1 to be an excellent marker for lymphatic development as it is expressed in the veins and the developing lymphatic vessels (26). We have also shown that treatment of zebrafish embryos with known lymphatic inhibitors reduced or abolished the expression of lyve1 mRNA (25).…”
Section: Introductionmentioning
confidence: 78%
“…We recently identified and characterized the expression of the zebrafish ortholog of lymphatic vessel endothelial hyaluronan receptor 1 (lyve1; ref. 25). LYVE-1 is extensively used as a marker for lymphatic vessels in mice and humans, and we found zebrafish lyve1 to be an excellent marker for lymphatic development as it is expressed in the veins and the developing lymphatic vessels (26).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations